Reviews of the Fund's Sovereign ARREARS Policies and Perimeter. (Policy Papers; Policy Paper, 2022)
This paper undertakes a comprehensive review of the Fund's sovereign arrears policies. Staff assesses that the Fund's Lending into Arrears to Private Creditors (LIA) policy (established in 1989 and last reviewed in 2002) remains broadly appropriate, while recommending some improvements given the experience gained over the last 20 years. Staff also sees merit in codifying the existing practice guiding the Fund in preemptive debt restructurings into a Fund policy, together with an amendment focusing on debt transparency. Given limited experience with the application of the LIOA policy (established in 2015), staff does not propose any amendments but only one restatement confirming current practice. Given recent developments in the international creditor community, staff proposes refining the Fund's arrears policies with respect to multilateral creditors. Finally, recent developments raise questions about the perimeter between official bilateral and private claims, with significant implications for the Fund's arrears policies.